Grounds of Efficient Use of Methods of Evaluation Procedure of the Projects in Capital Budgeting - Shmorgun, Nataliya (Podstawy efektywnego wykorzystania metod oceny projektów w budżetowaniu kapitałowym, 2010)
There are several methods of evaluation procedure of the projects in capital budgeting. Every method has some specific aspects and may be used autonomically or in combination with others. Many firms specify a limit on the overall budget for capital spending. Capital rationing is concerned with the problem of selecting the mix of acceptable projects, which provides the highest overall NPV. The profitability index (PI) is used widely in ranking projects competing for limited funds. The NPV method generally gives correct ranking, since the cost of capital (CC) is a more realistic reinvestment rate. The most important question for Ukraine is the question about financing of investment and innovation. The complex analysis of the statistical monitoring of innovation activity in Ukraine in 2007 indicated that a unit weight of own resource was 74% (for 90% enterprises), 18.5% was the credit facilities, 3% was a foreign investors’ resource, 1.3% was the public finance, 0.2% was a domestic investors’ resource [1]. The new Ukraine government has to give its careful consideration for investment problem.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 196-172
Keywords: efficient; methods of evaluation; projects; capital budgeting